2022
DOI: 10.1186/s12967-022-03626-x
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression IL-15 receptor alpha with IL-15 reduces toxicity via limiting IL-15 systemic exposure during CAR-T immunotherapy

Abstract: Background Chimeric antigen receptor (CAR)-T cell therapy is a powerful adoptive immunotherapy against both B-cell malignancies and some types of solid tumors. Interleukin (IL) -15 is an important immune stimulator that may provide ideal long-term persistent CAR-T cells. However, higher base line or peak serum IL-15 levels are also related to severe toxicity, such as cytokine release syndrome (CRS), graft-versus-host disease (GVHD), and neurotoxicity. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…It enhances the proliferation of human NK, CD4 + and CD8 + T cells in humanized mice [ 28 , 29 ], and exhibits potent immunostimulatory effects on NK, NKT and CD8 + T cells [ 30 , 31 ]. It is demonstrated that CAR-T cells secreting IL-15/IL-15Ra complex display comparable efficacy as secreting IL-15 alone with reduced adverse effects in hematological cancer [ 32 ]. In this study, we constructed the IL-15Rα into the extracellular region of CAR structure, which enhanced the anti-tumor effects of CAR-T cells against gastric cancer compared with conventional CAR-T.…”
Section: Discussionmentioning
confidence: 99%
“…It enhances the proliferation of human NK, CD4 + and CD8 + T cells in humanized mice [ 28 , 29 ], and exhibits potent immunostimulatory effects on NK, NKT and CD8 + T cells [ 30 , 31 ]. It is demonstrated that CAR-T cells secreting IL-15/IL-15Ra complex display comparable efficacy as secreting IL-15 alone with reduced adverse effects in hematological cancer [ 32 ]. In this study, we constructed the IL-15Rα into the extracellular region of CAR structure, which enhanced the anti-tumor effects of CAR-T cells against gastric cancer compared with conventional CAR-T.…”
Section: Discussionmentioning
confidence: 99%
“…To further prolong the persistence of infused T cells, stable IL-15/IL-15Rα complexes were incorporated to induce and sustain the expansion of the CD62L + and CCR7 + central memory T cell (Tcm) phenotype ex vivo resulting in augmented efficacy of adoptive immunotherapy [ 114 ]. As a result, efforts have been made to optimize the IL-15/IL-15Rα structure to achieve a higher proportion of infused T cells with stemness and greater antitumor potency in ACT [ 115 ]. In addition to its incorporation in ex vivo precultures, IL-15 and its receptor complex have been integrated into CAR engineering to maintain T SCM expansion in vivo for durable responses [ 116 122 ].…”
Section: Four Cytokines Of the γC Family Regulate T Cell Stemnessmentioning
confidence: 99%
“…Other strategies to improve the efficacy of CAR-T therapy in metastatic prostate cancer include developing dual-antigen CARs to mitigate antigen escape and tumor heterogeneity [ 116 ]. Moreover, “armored” CARs, co-expressing cytokines such as IL-12, IL-15, or IL-7/Chemokine (C-C motif) ligand 19 (CCL19), have demonstrated superior proliferative capacity, metabolic fitness, persistence, and anti-tumor efficacy compared to conventional CARs devoid of cytokine support [ 117 , 118 ]. The strategic combination of prostate cancer-targeted CAR T cells with PD-1 checkpoint inhibition or immunomodulatory drugs has also been studied in pre-clinical models [ 119 ].…”
Section: Chimeric Antigen Receptor (Car) T Cell Therapymentioning
confidence: 99%